THE CORRELATION BETWEEN THE PERCEPTION OF PROJECT-BASED DRAMA ACTIVITIES AND READING ACHIEVEMENT OF THE TENTH GRADERS OF SMA SRIJAYA NEGARA PALEMBANG - Veroricca, Viranny (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2023)
The objectives of this research are to find out the perception of the students of project-based drama activities, students’ reading achievement, and the correlation between them. The participants of this study were 34 students of the tenth-grade SMA Srijaya Negara Palembang. The instruments used are questionnaire and reading test. The questionnaire was a project-based drama activities questionnaire adapted from Fiftinova, Inderawati, and Rosmalina in 2018 which proposed by Teresa in 2007. The reading test consisted of several narrative texts with 30 multiple-choice items that were adjusted to the students’ reading level. The reading test was categorized by using a passing grade from the school. The respondents were categorized as poor and good achievers according to the final score they received. The findings showed that 100% of the students were in the poor category of reading. The adapted questionnaire was administered to the 34 students. It was found that there were 3% of the students perceived project-based drama activity negatively and 97% of the students viewed project-based drama activity positively. To find out the correlation, Pearson Product Moment Correlation Coefficient was used in SPSS version 25. The result of Pearson Product Moment Correlation Coefficient showed that there was no significant correlation between the perception of project-based drama activities and students’ reading achievement because the p-value (0.568) was higher than (0.05).